New Public Sphere dan Perkembangan Teknologi Media Sosial di Kawasan MENA (Middle East and North Africa): Studi Kasus Peranan Media InternasionalterhadapPembentukan Social Networking dalam Egyptian Revolution - Ajeng Rizqi Rahmanillah (Populis : Jurnal Sosial dan Humaniora, 2018)
ABSTRACT Massive movement of the Egyptian people, called the Egyptian Revolution, is part of a wave of democratization of the Arab Spring in the Middle East and North Africa.The purpose of this essay is to provide information about the influence of new public sphere and media technology, to the civil society movement in the region. The public sphere is the space of communication of ideas and projects that emerge from society and are addressed to the decision makers in the institutions of society. The global civil society is the organized expression of the values and interests of society. The relationships between government and civil society and their interaction via the public sphere define the polity of society. This essay is a qualitative study using the case study method. The results of this study showed that the development of global communication media has a significant influence on the civil society to develop their skills in using information technology. This has led to the Arab Spring in Tunisia became a successful spark that triggered the revolution in Egypt. Phase emergence of Reformers in the Arab Spring wave of democratization in Egypt indicate that the movement of the Reformers strongly associated with one of the instruments of mass communication become public means of expression, to spread the idea, and eventually forms a networking in a short time. Keywords: New Public Sphere, social media, social movement, egyption revolution